PROFIL POLA ASUH ORANG TUA DI SMAN 1 BONJOL DAN IMPLIKASINYA TERHADAP BIMBINGAN DAN KONSELING - Abdul Gani; Suryadi; Joni Edison (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study is motivated by the important role of parenting styles in shaping students’ personality, attitudes, and behavior, which in turn influence the need for guidance and counseling services at school. The purpose of this research is to describe the profile of students’ parenting styles at SMAN 1 Bonjol, including authoritarian, democratic, and permissive parenting styles, and to examine their implications for guidance and counseling services. This study employed a quantitative approach with a descriptive research design. The research subjects were 175 students of Grade XI Phase F at SMAN 1 Bonjol, selected through simple random sampling from a population of 313 students. The instrument used was a Likert-scale questionnaire consisting of 44 valid and reliable statements. Data were analyzed using descriptive statistics in the form of percentages. The results showed that the overall profile of parenting styles was in the moderately high category, with a percentage of 90.86%, indicating variations in the application of democratic, permissive, and authoritarian parenting styles. The implication of these findings highlights the need for school counselors to develop services focused on strengthening positive communication between parents and students, providing information services and psychoeducation on conducive parenting styles, and fostering collaboration between schools and parents to support students’ optimal development.